(untitled) (Bangladesh Journal of Zoology, 2025)
A total of five captive northern pig-tailed macaques (Macaca leonina) were observed from October 2022 to May 2023 using a structured ethogram to understand their behavioural patterns at Chittagong Zoo, Bangladesh. We detected nine activity patterns along with some abnormal behaviours using scan sampling methods with 5-minutes intervals. Diurnal and seasonal fluctuations in the behaviours were explicitly noticed. Locomotion was the highest (46.11%) time-consuming behaviour, followed by resting and grooming while bathing was the activity on which the macaques spent the lowest time (0.60%). M. leonina was mostly (29.44%) active during 09:00-11:00 h and engaged in less (18.41%) activity in the afternoon (03:00-05:00 h), which may be due to the captive environment. Seasonal patterns showed increased activity (25.59%) in late autumn and decreased activity (24.26%) in summer. These activities did not differ significantly within the pre-determined period (t = 1.95; P > 0.05). The macaques were found to be depressed for more time (24.36%) compared to other atypical activities such as debris eating, stereotypic pacing, begging, cage bar biting, etc. Time spent on these behaviors varied significantly during the study period (t = 3.62, P < 0.05). The unusual group structure, lack of captivity enrichment, and presence of the visitors – were assumed as the influences behind these abnormalities. Finally, we compared behavioural activities of captive M. leonina with activity patterns of wild groups published in the literature. Bangladesh J. Zool. 52(3): 323-336, 2024